2019
DOI: 10.1038/s41436-018-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors among unaffected participants following receipt of variants of uncertain significance in cardiomyopathy-associated genes

Abstract: Positive VUS results can be returned to apparently unaffected individuals with modest use of healthcare resources, minimal behavioral changes, and favorable psychological reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…While most participants in our study mentioned they would take the result to their doctors, few raised the intention to share the result with their relatives. Similar to what was reported in other studies (Miller et al, 2019;Smit et al, 2016), one participant mentioned that a letter can be an effective tool to review the information at a later time and to share this information with family members. The letter used in our study was not specifically designed to be shared with family members; however, family communication tools and letters have been developed and used in other studies, which could be used in combination with our letter (Kardashian et al, 2012;van der Roest et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…While most participants in our study mentioned they would take the result to their doctors, few raised the intention to share the result with their relatives. Similar to what was reported in other studies (Miller et al, 2019;Smit et al, 2016), one participant mentioned that a letter can be an effective tool to review the information at a later time and to share this information with family members. The letter used in our study was not specifically designed to be shared with family members; however, family communication tools and letters have been developed and used in other studies, which could be used in combination with our letter (Kardashian et al, 2012;van der Roest et al, 2009).…”
Section: Discussionsupporting
confidence: 64%
“…However, giving the result directly to patients allows them to manage their health information and share it with providers without access to the specific EHR where the result was deposited (Adler-Milstein et al, 2017;Myrick et al, 2019). Furthermore, with a patient-initiated approach, patients are engaged with their health information, which may serve as a reminder for recommended health behaviors beyond those pertaining to the result at hand (Miller et al, 2019). Future research could expand on prior work to study the effectiveness of a combination of approaches whereby results are deposited in the EHR and provided directly to patients (Williams et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More participants in the MMR study who received an IRR indicating a pathogenic mutation took further steps to discuss screening than those who were negative [ 8 ]. In a study of 68 individuals without cardiomyopathy who had received VUS for a cardiomyopathy gene, 15 went on to engage in health-related behavior change: nine had cardiac testing (for some of whom there were clinical indications) and 12 made lifestyle changes [ 205 ]. The study of healthy individuals who were randomized to receive testing for either AD+CAD or AD alone showed that 57% reported changing at least one health behavior at 12 months in response to genetic risk disclosure [ 210 ].…”
Section: Experiences With Receiving or Returning Resultsmentioning
confidence: 99%
“…Value in having an answer or a name [174,177] Potential for surveillance, early disease detection, access to treatment [9,87,153,177,182,198] Knowledge for children and ability to share information with family [87,153] Reproductive planning [177] Empowerment and greater sense of control [87,174] Benefit to science [177] Behavior change Some behavior change [9,31,100,186,200,205] No or minimal behavior change [8, 79, 87, 183, 198, 206, 207] [194] https://doi.org/10.1371/journal.pone.0258646.t007…”
Section: Perceptions Of Utility Participants Patients Publicsmentioning
confidence: 99%
“…Therefore, when choosing a genetic testing panel, using the largest available panel will maximize the likelihood of detecting a likely pathogenic or pathogenic variant. This approach also increases the likelihood of variants of uncertain significance, but observational studies do not detect an adverse effect on patients upon learning of VUSs [ 43 , 44 ]. Furthermore, the detection of suspicious VUSs creates an opportunity for resolution of the VUS toward pathogenic or benign if other affected family members are tested.…”
Section: Genes Implicated In Monogenic Dominant Dcmmentioning
confidence: 99%